Analysis of Competitiveness and Government Policy Impact in Batik Pekalongan - Ayu Cahyaning Kesuma; P Eko Prasetyo (Economics Development Analysis Journal, 2019)
The aim of this study is to analyze the competitiveness and impact of government policy and policy simulation on Batik SMI (Small and Medium Industry) in Pekalongan City. This research used quantitative research method by using Policy Analysis Matrix (PAM) analysis tool and policy simulation model. Sampling techniques which were used in this research were Cluster Random Sampling and Proportional Random Sampling. The results of PAM analysis showed that Batik SMI in Pekalongan City had comparative competitiveness and competitive competitiveness. Government policy has been able to protect Batik SMI in Pekalongan City, especially from the input factor side. Another policy alternative which still can be tolerated to maintain and improve competitiveness is by giving 20% Basic Electricity Tariff (BET) subsidy, 10% coloring drug subsidies, and an additional 5% value added, For the owner of Pekalongan Batik SMI it is suggested that they should be able to maintain their competitiveness in terms of increasing their effectiveness, efficiency and productivity, and for the government it is necessary to review the policies from the output side in order to protect Batik SMI in Pekalongan City.